Interface microstructure of porous Ni-Ti and Co-Cr-Mo powder alloy couple fabricated by SHS process - Kurt, B.; Somunkiran, I. (Maney Publishing, 2008)
In this study, porous Ni-Ti and Co-Cr-Mo alloy couple was fabricated by powder metallurgy (PM) process. With this aim, Ni-Ti and Co-Cr-Mo alloys powder was compacted into the mould one by one with Co-Cr-Mo being the one side and Ni-Ti the other side. Then, Ni-Ti side of the specimen was synthesised by self-propagating high temperature synthesis (SHS) process. At the end of the SHS process (after the SHS process), the porous Ni-Ti alloy has occurred. Finally, the specimen was sintered at 1050 degrees C into argon atmosphere. Scanning electron microscope with energy dispersive X-ray spectroscopy and X-ray diffractometer were used to characterise the microstructure and composition. It was seen from the results that porous Ni-Ti and Co-Cr-Mo alloy couple was successfully fabricated by PM process.
Keywords: Porous Ni-Ti; Co-Cr-Mo alloy; Powder metallurgy; Microstructure